Influence of multi extrusion die process on mechanical and chemical behavior of 2024-T3 alloy - Razooqi, Ahmed Ibrahim; Abbas, Naseer M.; Ghazi, Sara Saad (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, a cold multi-pass extrusion process for a 15mm in diameter solid 2024-T3 aluminum alloy rod was carried out using three dies to obtain three different diameters of 14mm, 13mm, and 12mm. The microstructure, hardness, and corrosion behavior were investigated before and after the extrusion process.
Keywords: Al 2024-T3; extrusion; plastic deformation; electrochemical corrosion